(untitled) (Journal of Information Systems and Technology Management, 2010)
The study verified the production area's key user opinions about needs being met by ERP through a survey conducted within industries from the State of São Paulo. The survey instrument is composed of 28 activities related to the production area, using the literature review on production management and ERP as a basis. Also, four dimensions for production activities were defined: Inventory Management Policies, Forecasts, MRP and MRP II. Activities were evaluated according to five different criteria: Needs Being Met, Ease of Use, Parameterization, Customization and Training. The questionnaire was answered by managers from 46 industries, composing a non-probabilistic sample with an accessibility criterion. The research is exploratory. The analysis of the obtained data broadly showed that ERPs meet the expectations of production managers. However, its most noteworthy aspect is the high number of activities that are not used by companies. It was noted that the higher the number of used activities, the higher the level of perception of needs being met.